(untitled) (Marketing Journal, 2025)
This article examines the development of the metallurgical industry in the region, the increase in demand for metal products used in construction, transport, energy and other sectors, small businesses operating in the Tashkent region, the activities of small businesses in various sectors of the regional economy, and the production, sale and processing of metal products.